The influence of spatial resolution on the spectral quality and quantification accuracy of whole‐brain MRSI at 1.5T, 3T, 7T, and 9.4T. Issue 2 (1st April 2019) - Motyka, Stanislav; Moser, Philipp; Hingerl, Lukas; Hangel, Gilbert; Heckova, Eva; Strasser, Bernhard; Eckstein, Korbinian; Daniel Robinson, Simon; Poser, Benedikt A.; Gruber, Stephan; Trattnig, Siegfried; Bogner, Wolfgang
Abstract : Purpose: Inhomogeneities in the static magnetic field ( B 0 ) deteriorate MRSI data quality by lowering the spectral resolution and SNR. MRSI with low spatial resolution is also prone to lipid bleeding. These problems are increasingly problematic at ultra‐high fields. An approach to tackling these challenges independent of B 0 ‐shim hardware is to increase the spatial resolution. Therefore, we investigated the effect of improved spatial resolution on spectral quality and quantification at 4 field strengths. Methods: Whole‐brain MRSI data was simulated for 3 spatial resolutions and 4 B 0 s based on experimentally acquired MRI data and simulated free induction decay signals of metabolites and lipids. To compare the spectral quality and quantification, we derived SNR normalized to the voxel size (nSNR), linewidth and metabolite concentration ratios, their Cramer‐Rao‐lower‐bounds (CRLBs), and the absolute percentage error (APE) of estimated concentrations compared to the gold standard for the whole‐brain and 8 brain regions. Results: At 7T, we found up to a 3.4‐fold improved nSNR (in the frontal lobe) and a 2.8‐fold reduced linewidth (in the temporal lobe) for 1 cm 3 versus 0.25 cm 3 resolution. This effect was much more pronounced at higher and less homogenous B 0 (1.6‐fold improved nSNR and 1.8‐fold improved linewidth in the parietal lobe at 3T). This had direct implications for quantification: the volume of reliably quantified spectra increased with resolution by 1.2‐fold and 1.5‐fold (when thresholded by CRLBs or APE, respectively). Conclusion: MRSI data quality benefits from increased spatial resolution particularly at higher B 0, and leads to more reliable metabolite quantification. In conjunction with the development of better B 0 shimming hardware, this will enable robust whole‐brain MRSI at ultra‐high field.